Extremely Increased Chloride Hunger in a Patient with Congenital Chloride Diarrhea: Non-Compliance Fake or New Pathology? - Heinz-Erian, Peter; Janecke, Andreas R.; Hofer, Stefanie; Pellkofer, Yasmin; Lanzersdorfer, Roland; Henkel, Martin; Kapral, Christine; Mueller, Thomas (Archives of Clinical and Medical Case Reports, 2021)
Congenital Chloride Diarrhea (CCD) is a rare autosomalrecessive disorder primarily characterized by severe watery diarrhea and fecal loss of large amounts of chloride. Maintaining adequate chloride status in adolescent CCDpatients is achieved by oral NaCl and KCl containing 3-4 mmol chloride/kg body weight/day. The best available control of chloride status is measuring chloride excretion in 24-hour urine collections. We here report a now twenty year-old caucasian CCD-patient with a compound heterozygous mutation in the SLC26A3 gene who presented with severe growth-retardation as evidenced by a Standard Deviation Score (SDS) for height of -3.57. His serum choride concentration was as low as 73 mmol/L and no chloride was detectable in his urine on many occasions over several years. Based on these laboratory findings the patient was repeatedly instructed to increase his salt intake which finally resulted in as much as six times the recommended dose of chloride, i.e.more than 20 - 25 mmol/kg/d. Only then he achieved measurable amounts of chloride in his urine and regained age-adequate growth. This paper should alert physicians to the possibility that in certain CCD patients salt intake reports in conjunction with laboratory results may falsely indicate the need for a much higher than usual chloride supplementation than hitherto reported. While non-compliance in adhering to physician´s prescriptions is believed to be the most probable cause, other potential etiologies, including medications driving chloride excretion, gut resection, infection/inflammation and novel as yet undiscovered genetic disorders in addition to SLC26A3-mutations should not be neglected.